2020
DOI: 10.1038/s41467-020-18276-0
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated immune cell recruitment orchestrated by FOXM1 impairs human diabetic wound healing

Abstract: Diabetic foot ulcers (DFUs) are a life-threatening disease that often result in lower limb amputations and a shortened lifespan. However, molecular mechanisms contributing to the pathogenesis of DFUs remain poorly understood. We use next-generation sequencing to generate a human dataset of pathogenic DFUs to compare to transcriptional profiles of human skin and oral acute wounds, oral as a model of “ideal” adult tissue repair due to accelerated closure without scarring. Here we identify major transcriptional n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
188
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(193 citation statements)
references
References 64 publications
5
188
0
Order By: Relevance
“…Our finding that high glucose environments reduce the recruitment of neutrophils to a tail wound is consistent with studies of diabetic foot ulcers [2, 4]. In mammals, high glucose environments have been shown to interfere with metabolites and enzymes related to neutrophil function [37].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our finding that high glucose environments reduce the recruitment of neutrophils to a tail wound is consistent with studies of diabetic foot ulcers [2, 4]. In mammals, high glucose environments have been shown to interfere with metabolites and enzymes related to neutrophil function [37].…”
Section: Discussionsupporting
confidence: 90%
“…Altered innate immune cell recruitment to wounds is a conserved feature of hyperglycaemia in mammals [4, 5, 2931]. To determine if this phenomenon was conserved in zebrafish embryos, we utilised the tail transection wound model which causes reproducible leukocyte recruitment [23] (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of chronic wounds is higher in older people with underlying pathologies including diabetes mellitus, vascular disease, and obesity [311]. The cellular programs restoring the skin barrier do not function properly in chronic wounds [308,312,313]. Impaired wound healing is characterized by accelerated keratinocyte proliferation, impaired migration, and fibrosis.…”
Section: Wound Pathophysiologymentioning
confidence: 99%
“…These hard-to-treat wounds pose a significant medical challenge; as their prevalence has steadily increased over time and only modest therapeutic advancements have come from animal studies [ 30 , 31 ]. While tremendous efforts have uncovered defects in cellular composition and function during the proliferative phase of repair, animal models have recently revealed that reduced activation of early inflammatory responses is associated with delayed healing [ 32 , 33 , 34 ]. Due to their role in ECM production, dermal mesenchymal cells have been studied in the context of ECM formation and maturation; however, emerging evidence has revealed that adipocytes and fibroblasts can also promote inflammation.…”
Section: Introductionmentioning
confidence: 99%